Program Kelompok Dukungan Sebaya Bagi Odhiv di Yayasan Mutiara Maharani - Aulia Putri Anggraini; Sokhivah Sokhivah (Sosial Simbiosis : Jurnal Integrasi Ilmu Sosial dan Politik, 2024)
Peer Support Groups have a meaningful role in the life of an ODHIV. ODHIV who received a peer support had a significant effect on changes in HIV identity, HIV knowledge, access to HIV services, HIV prevention behaviors and positive activities compared to ODHIV who did not receive peer support. The purpose of this study is to find out the process of peer support group program activities. This study was carried out using descriptive qualitative research methods, using data collection with interview, observation and documentation techniques. The results of the study show that this peer support group program has been running and implemented optimally and the ODHIV members have shown an increase in self-change through activities that have been planned according to the needs of the ODHIV, namely family groups, socialization, counseling, self-help groups, capacity building and also mobile visiting.